Functional nano-structuring of thin silicon nitride membranes - Matějka, Milan; Krátký, Stanislav; Říháček, Tomáš; Knápek, Alexandr; Kolařík, Vladimír (Sciendo, 2020)
The paper describes the development and production of a nano-optical device consisting of a nano-perforated layer of silicon nitride stretched in a single-crystal silicon frame using electron beam lithography (EBL) and reactive ion etching (RIE) techniques. Procedures for transferring nanostructures to the nitride layer are described, starting with the preparation of a metallic mask layer by physical vapor deposition (PVD), high-resolution pattern recording technique using EBL and the transfer of the motif into the functional layer using the RIE technique. Theoretical aspects are summarized including technological issues, achieved results and application potential of patterned silicon nitride membranes.

The paper describes the development and production of a nano-optical device consisting of a nano-perforated layer of silicon nitride stretched in a single-crystal silicon frame using electron beam lithography (EBL) and reactive ion etching (RIE) techniques. Procedures for transferring nanostructures to the nitride layer are described, starting with the preparation of a metallic mask layer by physical vapor deposition (PVD), high-resolution pattern recording technique using EBL and the transfer of the motif into the functional layer using the RIE technique. Theoretical aspects are summarized including technological issues, achieved results and application potential of patterned silicon nitride membranes.
Functional nano-structuring of thin silicon nitride membranes
Keywords: membrane; nano optical device; electron optics; electron beam lithography; silicon nitride; reactive ion etching; silicon etching; microfabrication; membrane; nano optical device; electron optics; electron beam lithography; silicon nitride; reactive ion etching; silicon etching; microfabrication